2022
DOI: 10.15587/1729-4061.2022.253146
|View full text |Cite
|
Sign up to set email alerts
|

Design and implementation of a fault tolerant web-based examination system for developing countries

Abstract: This paper presents the development of a web-based examination system that focuses on automated resolution of faults such as power, network, or component failure that may occur when an e-learning system is used to conduct an examination. This system can withstand various challenges that hinder the adoption of e-learning technologies in developing countries. This is important because it will reduce the time and cost involved in conducting large scale examinations by tertiary institutions without the need to upg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…3) Personalized Learning/Test-based Content retrieves the learner's profile and (a) provide adaptive contents from model, (b) retrieve the personalized learner's questions in lieu of learned contents, and (c) stores them as temporary session to ease access to the contents and ensure that as the knowledge-base grows, performance is not degraded with the increase in users and the system shift between profiles [32]. Fig.…”
Section: Proposed Adaptive Architecture For the Learner-centricmentioning
confidence: 99%
See 1 more Smart Citation
“…3) Personalized Learning/Test-based Content retrieves the learner's profile and (a) provide adaptive contents from model, (b) retrieve the personalized learner's questions in lieu of learned contents, and (c) stores them as temporary session to ease access to the contents and ensure that as the knowledge-base grows, performance is not degraded with the increase in users and the system shift between profiles [32]. Fig.…”
Section: Proposed Adaptive Architecture For the Learner-centricmentioning
confidence: 99%
“…The implications is: (a) non-access to physical infrastructure for learning, (b) yielded increased learning inequality and losses resulting from the stratified Internet access [28], [29], (c) learning disparities resulting from digital revolution/integration across a variety of learning platforms in www.ijacsa.thesai.org Nigeria (uLesson etc. ), (d) the learner psychomotor and cognition health stability to adjust to blended, ICT-richlearning paradigm as a new reality, and (e) learner adaptabilities to new complex logistics in these new paradigm, and other costs [30]- [32]. These, are determined through formative and summative testing.…”
Section: Introductionmentioning
confidence: 99%
“…The authors evaluated the responses using the semantic relational characteristic. Eko et al . (2022) describe the development of a web-based examination system that focuses on the automatic resolution of issues such as power failure, network issues and component failure that may arise during the examination.…”
Section: Review Of Literaturementioning
confidence: 99%
“…According to reports, the disproportionate impact on students from disadvantaged circumstances, which has the potential to contribute to disparate achievement, is a factor impacting access to stable technology enabling online exam portals (Alruwais et al ., 2018; Fuller et al ., 2020). Eko et al . (2022) propose in their study that the development of web-based examination systems should prioritize the automatic resolution of problems such as power outages, component failures and so on that may arise when the system is used to administer online tests.…”
Section: Introductionmentioning
confidence: 99%
“…In a recent study, Eko et al showed a fault-tolerant, web-based exam system targeted for developing countries [8].…”
Section: Related Workmentioning
confidence: 99%